1976
DOI: 10.1148/121.3.521
|View full text |Cite
|
Sign up to set email alerts
|

The Midsternal Stripe: A Sign of Dehiscence Following Median Sternotomy

Abstract: Sternal dehiscence is a recognized complication of median sternotomy in 2.5-4.8% of patients. The authors describe the prognostic significance of a lucent midsternal stripe which was seen in 12 patients over a two-year period. Sternal dehiscence requiring surgical revision developed in 4, and radiological suspicion preceded clinical evidence of dehiscence in 3 of them. A review of 100 consecutive median sternotomies revealed that sternal dehiscence did not develop in any patient who did not have a midsternal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The midsternal stripe sign was first described by Escovitz et al [8], who detected a midsternal radiolucency in 12 of 250 postoperative patients during a 2-year period and found that sternal dehiscence developed in four of these patients. A review by the same authors of the cases of 100 consecutive patients who had undergone median sternotomy revealed that sternal dehiscence did not develop in any patient who did not have a midsternal stripe.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The midsternal stripe sign was first described by Escovitz et al [8], who detected a midsternal radiolucency in 12 of 250 postoperative patients during a 2-year period and found that sternal dehiscence developed in four of these patients. A review by the same authors of the cases of 100 consecutive patients who had undergone median sternotomy revealed that sternal dehiscence did not develop in any patient who did not have a midsternal stripe.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, there has been a longstanding interest in determining whether radiography could be used in identifying this complication [8][9][10]. Two major radiographic signs have been described: the midsternal stripe sign and sternal wire displacement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations